Interpersonal and intrapersonal leadership competencies: an interpretative phenomenological analysis on effective leadership strategies - Aquino, Marion Koreen Andrea; Bumacod, Alicia Mae; Calapine, Arizzandra Gerriz; Yaco, Jan Marie Therese; Dimailig, Margarett Luz; Amores, Avon Pearl; Francisco, Joseph (Frontiers in Psychology, 2025)
IntroductionIn today’s dynamic business environment, unforeseen challenges have become increasingly prevalent as markets evolve. Effective leadership is critical to organizational success, requiring leaders who can efficiently manage both their tasks and employees. Thus, it is valuable to explore and identify competencies possessed by competent leaders.MethodsThe study utilized an Interpretative Phenomenological Analysis (IPA) approach to have a detailed exploration of the strategies and practices leaders find most effective in navigating complex organizational challenges, such as strategy adoption, teamwork improvement, client relationship management, ethical decision-making, and industry adaptation. Purposive sampling was used to select five Filipino organizational leaders from diverse industries. The small yet varied sample allowed for an in-depth analysis of personal experiences while ensuring that the findings resonate broadly within the Philippine organizational context. Data collection involved in-depth, semi-structured interviews conducted via Microsoft Teams. The interviews were transcribed, coded, and thematically analyzed in accordance with IPA guidelines.Results and discussionCompetencies were categorized under the five competency areas, with further exploration of interpersonal and intrapersonal impacts. The iterative analysis revealed recurring competencies across all areas. Intrapersonal competencies included personal growth through change, leadership through vision and resilience, continuous learning, innovative thinking and openness, and resilience in personal challenges. Meanwhile, interpersonal competencies included collective innovation, effective communication, transformative client engagement, empathetic conflict resolution, and building adaptive teams. These enabled leaders to maintain their competence in navigating organizational challenges, including the pandemic, technological advancements, and evolving workforce dynamics. These findings suggest that effective leadership operates on both individual and interpersonal levels. Leaders’ internal processes significantly influence their relationships and interactions. Resilient leaders stabilize teams during crises, while a commitment to continuous learning fosters innovation and collaboration. Strong communication skills promote knowledge sharing and strengthen relationships with clients, subordinates, and stakeholders. Empathetic leadership reduces stress and conflict, creating healthier work environments. Finally, leaders’ motivation and dedication inspire team transformation and adaptability. Thus, these leadership competencies are instrumental in sustaining a competitive edge and driving organizational growth amidst a dynamic business environment.